Prevalence and risk factors of micronutrient deficiencies pre- and post-antiretroviral therapy (ART) among a diverse multicountry cohort of HIV-infected adults. Issue 1 (February 2016) - Shivakoti, Rupak; Christian, Parul; Yang, Wei-Teng; Gupte, Nikhil; Mwelase, Noluthando; Kanyama, Cecilia; Pillay, Sandy; Samaneka, Wadzanai; Santos, Breno; Poongulali, Selvamuthu; Tripathy, Srikanth; Riviere, Cynthia; et al.
Summary: Background & aims: HIV-infected adults have increased risk of several individual micronutrient deficiencies. However, the prevalence and risk factors of concurrent and multiple micronutrient deficiencies and whether micronutrient concentrations change after antiretroviral therapy (ART) initiation have not been well described. The objective of this study was to determine the prevalence and risk factors of individual, concurrent and multiple micronutrient deficiencies among ART-naïve HIV-infected adults from nine countries and assess change in micronutrient status 48 weeks post-ART initiation. Methods: A random sub-cohort (n = 270) stratified by country was selected from the multinational PEARLS clinical trial (n = 1571 ART-naïve, HIV-infected adults). We measured serum concentrations of vitamins A, D (25-hydroxyvitamin), E, carotenoids and selenium pre-ART and 48 weeks post-ART initiation, and measured vitamins B6, B12, ferritin and soluble transferrin receptor at baseline only. Prevalence of single micronutrient deficiencies, concurrent (2 coexisting) or conditional (a deficiency in one micronutrient given a deficiency in another) and multiple (≥3) were determined using defined serum concentration cutoffs. We assessed mean changes in micronutrient concentrations from pre-ART to week 48 post-ART initiation using multivariable random effects models. Results: Of 270 participants, 13.9%, 29.2%, 24.5% and 32.4% had 0, 1, 2 and multiple deficiencies, respectively. Pre-ART prevalence was the highest for single deficiencies of selenium (53.2%), vitamin D (42.4%), and B6 (37.3%) with 12.1% having concurrent deficiencies of all three micronutrients. Deficiency prevalence varied widely by country. 48 weeks post-ART initiation, mean vitamin A concentration increased (p < 0.001) corresponding to a 9% decrease in deficiency. Mean concentrations also increased for other micronutrients assessed 48 weeks post-ART (p < 0.001) but with minimal change in deficiency status. Conclusions: Single and multiple micronutrient deficiencies are common among HIV-infected adults pre-ART initiation but vary between countries. Importantly, despite increases in micronutrient concentrations, prevalence of individual deficiencies remains largely unchanged after 48 weeks on ART. Our results suggest that ART alone is not sufficient to improve micronutrient deficiency.